Soil organic matter characteristics of four soil types under different conservation strategies across Hubei Province - Wei Yang; Yangbo He; Xingsheng Song; Lirong Lin; Zhengchao Tian; Ying Zhou (Agricultural & Environmental Letters)
Abstract Soil organic matter (SOM) plays key roles in sloping land erosion control. This study explores SOM content across Hubei Province, China, focusing on four soil types under various conservation strategies. Field samples (n = 243) were collected under 27 monitoring sites employing diverse conservation strategies in runoff plots. Results indicated substantial variability in SOM content among soil types, with calcareous soils exhibiting the highest levels (12.63 g kg−1). Conversely, red soils displayed the lowest SOM content (6.32 g kg−1). However, short‐term conservation strategies and their interaction with soil type did not significantly influence SOM. The findings underscore the intricate relationship between soil types and SOM dynamics. This study contributes to the understanding of SOM dynamics in diverse landscapes, offering valuable guidance for policymakers and land managers to apply practices in mitigating erosion and enhancing soil health. Core Ideas Soil organic matter (SOM) characteristics focusing on four soil types under various conservation strategies were studied in Hubei Province. Calcareous soils exhibited the highest levels of SOM. Short‐term conservation strategies have no significant effect on SOM for each soil type. Land managers need proper practices to retain soil organic matter in mitigating erosion and enhancing soil health.